2010
DOI: 10.1073/pnas.1002830107
|View full text |Cite
|
Sign up to set email alerts
|

Multicatalytic, asymmetric Michael/Stetter reaction of salicylaldehydes and activated alkynes

Abstract: We report the development of a multicatalytic, one-pot, asymmetric Michael/Stetter reaction between salicylaldehydes and electrondeficient alkynes. The cascade proceeds via amine-mediated Michael addition followed by an N-heterocyclic carbene-promoted intramolecular Stetter reaction. A variety of salicylaldehydes, doubly activated alkynes, and terminal, electrophilic allenes participate in a one-step or two-step protocol to give a variety of benzofuranone products in moderate to good yields and good to excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(50 citation statements)
references
References 69 publications
1
49
0
Order By: Relevance
“…As the Stetter reaction is significantly influenced by olefin geometry (E-isomers react with higher yield and enantioselectivity) the authors performed the reaction sequence with allenoates 206 (Scheme 31). 89 These starting materials (as well as 201) formed the intermediate aldehydes with high E-selectivity, whereas ketoalkynoates gave mixtures of E and Z isomers. Thus, employing 73 and 206 in a sequential multicatalytic reaction afforded the desired products 207 in reasonable yields and with up to 98% ee (Scheme 31).…”
Section: Combinations With Secondary Amine Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the Stetter reaction is significantly influenced by olefin geometry (E-isomers react with higher yield and enantioselectivity) the authors performed the reaction sequence with allenoates 206 (Scheme 31). 89 These starting materials (as well as 201) formed the intermediate aldehydes with high E-selectivity, whereas ketoalkynoates gave mixtures of E and Z isomers. Thus, employing 73 and 206 in a sequential multicatalytic reaction afforded the desired products 207 in reasonable yields and with up to 98% ee (Scheme 31).…”
Section: Combinations With Secondary Amine Catalystsmentioning
confidence: 99%
“…Interestingly, the tertiary amine (198 or 199) not the carbene 160 acts as nucleophilic catalyst for the Michael reaction although both are present from the outset of the reaction, which was confirmed by control experiments. 89 Further investigations indicated that the enantioselectivity of the reaction is possibly enhanced by traces of strong hydrogen bonding donors, such as catechols, 91 derived from Dakin-oxidation of salicylaldehydes. When the reaction was performed stepwisely the final products were isolated in good yields, however, in lower and more uniform enantioselectivities.…”
Section: Combinations With Secondary Amine Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…This selectivity, governed by the identity of the catalytic base used, promotes highly enantioselective hetero-Diels-Alder reaction over homoenolate-mediated cyclopentene formation (9). Alternatively, Filloux et al (10) used an achiral N-heterocyclic carbene catalyst in combination with a chiral prolinol derivative to affect an asymmetric cascade involving a Michael addition and subsequent Stetter reaction sequence, promoted by their respective catalysts. Through this protocol, they showed that a family of asymmetric benzofuranones could be accessed by combining salicylaldehydes with alkynes or allenes.…”
Section: Desymmetrizationsmentioning
confidence: 99%
“…This section highlights examples from the fields of iminium, enamine, dienamine, and singly occupied molecular orbital (SOMO) catalysis, in which mechanistic insight, reaction partner scope, or product accessibility has been expanded in significant ways. The next classification of articles is somewhat broader and includes those modes of activation that are catalyzed by nonamine-centered Lewis bases (7)(8)(9)(10). Although there are fewer established modes of generic activation that fall into this category, the potential for reaction discovery in this arena is evident from the highlighted examples, which represent quite disparate modes of activation arising from phosphorus, chalcogen, and N-heterocyclic carbene catalysts.…”
mentioning
confidence: 99%